2022
DOI: 10.3389/fendo.2022.986303
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic comparison followed by cross-validation of enzyme-linked immunosorbent assay to reveal potential biomarkers of diabetic retinopathy in Chinese with type 2 diabetes

Abstract: PurposeTo identify the biomarkers in the critical period of development in diabetic retinopathy (DR) in Chinese with type 2 diabetes using targeted and untargeted metabolomics, and to explore the feasibility of their clinical applicationMethodsThis case-control study described the differential metabolites between 83 Chinese type 2 diabetes mellitus (T2DM) samples with disease duration ≥ 10 years and 27 controls matched cases. Targeted metabolomics using high-resolution mass spectrometry with liquid chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Recent studies revealed that the pathological processes of DR were associated with long-term metabolic disturbances ( 9 , 27 , 28 ). With the advancement of metabolomics, metabolites and metabolic pathways associated with DR are continuously being discovered ( 10 , 27 , 29 ). These crucial metabolites are often considered potential biomarkers for disease prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that the pathological processes of DR were associated with long-term metabolic disturbances ( 9 , 27 , 28 ). With the advancement of metabolomics, metabolites and metabolic pathways associated with DR are continuously being discovered ( 10 , 27 , 29 ). These crucial metabolites are often considered potential biomarkers for disease prediction.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a substantial amount of research has reported potential novel biomarkers for DR in human plasma in samples from patients with T1D or T2D with different disease durations and DR stages, including citrulline, indoleacetic acid, 1-methylhistidine, chenodeoxycholic acid, eicosapentaenoic acid, glutamine and glutamic acid, 1,5-gluconolactone, 2deoxyribonic acid, gluconic acid, fumaric acid, uridine, acetic acid, and cytidine [13,18,[20][21][22][23][24][25][26][27][28][29]. Several of these, such as 3,4-dihydroxybutyric acid (3,4-DHBA), were validated as independent risk markers for DR progression in a study of 648 individuals with T1D [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, this association lost significance after adjusting for creatinine values. Notably, a comparison between targeted and non-targeted metabolomics results unveiled the ability of citrulline and carnitine to differentiate the severity of DR using both approaches [ 55 ]. Combined with proteomics research, it has been discovered that tryptophan metabolism also plays a crucial role in the development of DR.…”
Section: Metabolomics In Diabetic Retinopathymentioning
confidence: 99%
“…NO is a crucial vasodilator that plays a vital role in maintaining vascular endothelial health [ 49 ]. Insufficient NO levels, combined with elevated levels of polyamines and proline, can lead to endothelial cell dysfunction and impaired vasodilation, and can also stimulate cell proliferation and fibrosis [ 55 ]. However, it should be noted that while arginine can stimulate insulin release in pancreatic β cells, poorly regulated arginine and citrulline levels can also contribute to retinal endothelial cell dysfunction [ 55 , 103 ].…”
Section: Dysregulation Of Metabolic Pathways In Drmentioning
confidence: 99%
See 1 more Smart Citation